(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The text points to the fundamental characteristics of Jovanaka Hrvaćanin’s works in the context of Serbian literature; it points to two thematically and formally different parts of her opus. The most valuable part of her oeuvre (Pesme neviđenom, novel Neviđeni and Zapisi) was written during the interwar period. It is filled with the central experience of authoress’ growing up and it reveals the basic characteristics of her poetics: conciseness, orientation to introspection, inner experiences and confiding in the worthy interlocutor. The spiritus movens of her creation and the basis of the coherence of the created text is her longing for an ideal, for love as an integral experience and the true other.